Effect of Kangaroo Mother Care on the Psychological Stress Response and Sleep Quality of Mothers With Premature Infants in the Neonatal Intensive Care Unit - Wei-yan Chen; Ying-ying Wu; Meng-yan Xu; Tao-Hsin Tung (Frontiers Media S.A., 2022)
ObjectiveTo investigate the effect of kangaroo mother care on the psychological stress response and sleep quality of mothers with premature infants admitted to the neonatal intensive care unit (NICU).MethodsA randomized controlled design was used to recruit participants. The study recruited 126 mothers of premature infants in the NICU from January 2019 to January 2020. The participants were divided into the experimental and control groups according to the random number table method (63 mothers per group). The control group was managed with conventional premature infant treatment, nursing programme, and discharge education, whereas the experimental group was managed with a 4-week kangaroo mother care intervention. The psychological stress state and sleep status of mothers with preterm infants in both the groups were evaluated using the Symptom Check List 90 (SCL-90) and Assens Insomnia Scale (AIS).ResultsAfter the intervention, the total SCL-90 score and factor scores such as coercion, interpersonal relationships, depression, anxiety, hostility and additional factors, were lower in the experimental group than those in the control group (P < 0.05). The total AIS score and the items such as night waking, total sleep time, total sleep quality, daytime mood and daytime body function were lower in the experimental group than those in the control group (P < 0.05).ConclusionsThe Kangaroo mother care approach can relieve adverse psychological stress and improve the sleep status of mothers of NICU premature infants after mother-infant separation. It can be promoted and used in mothers of premature infants in the NICU to enhance physical and mental health.